PREVENTION OF CORRUPTION IN THE STATE EDUCATION: THE SINGAPORE AND JAPAN EXPERIENCE (World Bulletin of Management and Law, 2023)
This article analyzes the issues of preventing corruption in the field of public education on the example of Singapore. The work carried out by Singapore in the field of public education, their positive experience was studied, the issues of intro-ducing their positive achievements into our national legislation and practice were analyzed.